Anti-commensal IgG Drives Intestinal Inflammation and Type 17 Immunity in Ulcerative Colitis - Castro-Dopico, Tomas (Immunity, 2019)
Inflammatory bowel disease is a chronic, relapsing condition with two subtypes, Crohn’s disease (CD) and ulcerative colitis (UC). Genome-wide association studies (GWASs) in UC implicate a FCGR2A variant that alters the binding affinity of the antibody receptor it encodes, FcγRIIA, for immunoglobulin G (IgG). Here, we aimed to understand the mechanisms whereby changes in FcγRIIA affinity would affect inflammation in an IgA-dominated organ. We found a profound induction of anti-commensal IgG and a concomitant increase in activating FcγR signaling in the colonic mucosa of UC patients. Commensal-IgG immune complexes engaged gut-resident FcγR-expressing macrophages, inducing NLRP3- and reactive-oxygen-species-dependent production of interleukin-1β (IL-1β) and neutrophil-recruiting chemokines. These responses were modulated by the FCGR2A genotype. In vivo manipulation of macrophage FcγR signal strength in a mouse model of UC determined the magnitude of intestinal inflammation and IL-1β-dependent type 17 immunity. The identification of an important contribution of IgG-FcγR-dependent inflammation to UC has therapeutic implications.